Where do multinationals locate profits: Evidence from country-by-country reporting - Tomáš Boukal (Charles University in Prague, Institute of Economic Studies (IES), 2024)
Multinational enterprises are increasingly using offshore locations to pay lower taxes on their profits. This behavior has distortive effects on the global economy, as the concentration of multinational activities mirrors global tax patterns. In this paper, I exploit the OECD country-by-country reporting statistics to analyze the determinants behind the location of profits. I find that profit allocation is sensitive to both effective tax rates and geographical proximity, confirming the significance of these factors in MNEs' tax planning strategies. Building on the work of Dharmapala and Hines (2009), this study also uncovers that MNEs are more likely to report profits to jurisdictions with superior governance quality, integrating both Global Governance Indicators and factors linked to financial secrecy. However, the findings indicate that tax haven jurisdictions exhibit a degree of reluctance when it comes to implementing recently introduced policies aimed at combating corruption and tax abuses.
Keywords: F23; G15; G28; H26; H32; 330; international taxation; tax havens; country-by-country reporting; gravity models; governance quality